Life-span development - Santrock, John W. (New York McGraw-Hill Higher Education, 2008)
The life-span perspective; Beginnings; Infancy; Early childhood; Middle and late childhood; Adolescence; Early adulthood; Middle adulthood; Endings.
Includes bibliographical references (p. R-1-R-84) and indexes.
Keywords: Developmental psychology -- Textbooks; Tâm lý học